The Complexity Role of Muslim Women in Java - Srifariyati Srifariyati; Muhamad Rifa'i Subhi (LPPM IAIN Parepare, 2023)
The study of gender cannot be separated from theological studies, because all religions have special treatment for women. The position of women in several religions and beliefs is placed as second class. As a result, the condition of women continues to be in a state of loss because of religious pretexts or legitimacy. This article discusses the basis of gender stereotypes in Islam, gender biased interpretation of the Qur’an, and gender equality in Islamic culture in Java. This study uses a library research approach. The result is that the Qur’an has explicitly tried to increase the dignity of women. This condition shows that Islam emphasizes that both men and women are given equal opportunities to achieve positions or degrees according to their abilities. These Islamic values ??are then firmly adhered to in realizing gender equality in Islamic culture in Javanese society, so that they can destroy perceptions of the position, dignity, and worth of men and women. Further research is needed that specifically addresses the role of Muslim women in the current era.